Tradisi Membuang Ayam di Jembatan Belik Gompeng pada Acara Pernikahan Masyarakat Desa Kandangmas Kecamatan Dawe Kabupaten Kudus dalam Perspektif Hukum Islam - Jatmiko Hary Sulistiyo; Muhammad Asrowi Elfath; Fazry Lamehan; Pauzi Muhammad; Ayub Mursalin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Javanese traditional weddings are an important event for the Javanese people, where many traditional ceremonial processions must be carried out. One of the things carried out by the people of Kandangmas Village is the tradition of throwing chickens on the Belik Gompeng Bridge during wedding ceremonies. This tradition is still carried out from generation to generation to this day without understanding its meaning and purpose. This research was conducted on one of the bridges in Kandangmas Village, Dawe District, Kudus Regency, namely the Belik Gompeng Bridge. This research aims to find out the meaning and purpose of people who still carry out this tradition, as well as looking at it from the perspective of Islamic law according to maslahah murlah. This research is included in the type of field research, where to obtain the data needed by researchers, they go into the field or the actual community. The type of research approach used is a descriptive qualitative approach. The data collection technique uses direct observation methods at the scene of the crime, interviews with traditional leaders, religious leaders, community leaders, and employees of the Kandangmas Village Hall. Based on the results of research, the tradition of throwing chickens on bridges is a tradition passed down from ancestors which is still being preserved. At first, chickens were a form of worship to the spirits that inhabited the bridge, but over time the chicken became a symbol of alms. The aim is to ask for safety so that the bride and her entourage will be given safety, good fortune and avoid bad luck.